A rapid, solid phase extraction (SPE) technique for the extraction and gas chromatographic determination lindane pesticide residue in tissue and milk - Yuningsih .; Sri Yuliastuti (Jurnal Ilmu Ternak dan Veteriner, 2005)
Organochlorine pesticide contamination in feed can cause residue in animal product (tissue and milk), so its become a problem in food safety. Solid phase extraction (SPE) has been carried out for determination organochlorine pesticide residues in food animal production. The technique was rapid, not costly and produce limited amount of hazardous-waste. Samples were homogenized with acetonitrile trough cartridge C18, eluted in fluorocyl column with 2% ether-petroleum or acetonitrile fortissue and milk samples respectively. The recoveries of tissue sample by addition lindane standard solution: 0.50 and 1.00 μg are 85.10 and 103.10% respectively, while that of milk with the addition of 0.50, 1.00 and 1.50 μg are 83.80, 88.69 and 91.24% respectively. Three replicates were carried out for every sample. According of validation criteria of FAO/IAEA the recovery for analysis of pesticide residues was 70-110%. Therefore, the method is applicable.     Key Words: Pesticide, Tissue, Milk, SPE, Gas Chromatography